FRI0464 GENOTYPING AND PHENOTYPING PATTERNS IN PATIENTS WITH CAPS IN RUSSIAN FEDERATION. (2nd June 2020) - Shingarova, M.; Alexeeva, E.; Dvoryakovskaya, T.; Savostyanov, K.; Pushkov, A.; Chistyakova, E.; Isaeva, K.; Chomakhidze, A.; Lomakina, O.; Denisova, R.; Mamutova, A.; Fetisova, A.; et al.
Abstract : Background: Cryopyrine-associated periodic syndromes (CAPS) are a group of rare congenital auto-inflammatory diseases (AID) that include diseases such as familial cold auto-inflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and CINCA/NOMID syndrome. At present, there are limited data on demographic and clinical features of children with CAPS in Russia. Objectives: To reveal demographic, genotype and phenotype characteristics in CAPS patients at the National Medical Research Center of Children`s health, Moscow, Russia. Methods: Retrospective study included 12 patients (7 females, 58.3%) with CAPS confirmed by next generation sequencing (NGS). Median age of disease onset was 5.7 (interquartile range (IQR) 0.5:12.8) years. Characteristics of disease onset as well as dynamics of disease activity during long-term treatment were evaluated. Results: At the onset, systemic features were as follows: fever in 11 (91.6%) patients, rash in 8 (66.7%), hepatosplenomegaly in 7 (58.3%) patients, and lymphadenopathy in 6 (50%). Active arthritis in the onset of the disease was in 9/12 patients (75%), presented by polyarthritis in 7/9 (77.8%), and oligoarthritis in 2/9 (22.2%). Two patients (16.7%) had cataract, one (8.3%) had bilateral uveitis, and one (8.3%) had optic atrophy. Sensorineural hearing loss was observed only in 3/12 (25%). Hydrocephalus was detected in 3/12 (25%). Delayed mental and psycho-speech development was observed in 6/12 (50%) patients. In 3/12 (25%), the development of MAS was recorded. All patients had nucleotide variants in NLRP3 gene. According to NGS results and clinical characteristics, 8/12 (66.7%) patients were diagnosed with MWS and 4/12 (33.3%) had CINCA/NOMID syndrome. In children with MWS, heterozygous variant c.2113C>A in NLRP3 gene was the most common (5/8 (62.5%) patients). One of 8 (12.5%) patients with novel heterozygous variant c.2861C>T was detected; also one child (12.5%) have heterozygous variant c.598G>A and one (12.5%) – heterozygous variant c.943A>G . Four patients with CINCA/NOMID syndrome also had heterozygous variants in NLRP3 gene: c.598G>A, c.2173C>A, c.1991T>C and c.796C>T . Prior to genetic testing, 12/12 (100%) patients received NSAIDs; 6/12 (50%) were treated with oral glucocorticoids (GC), 3/12 (25%) – with intravenous GC, 2/12 (22.2%) – with methotrexate. Biologics treatment included: 5/12 (41.7%) CAN, 4/12 (33.3%) tocilizumab, and 1/12 (8.3%) etanercept. After genetic testing, 7/12 (58.3%) patients were successfully switched to CAN. Only 1/12 (8.3%) child with MWS developed secondary inefficiency on CAN treatment. Conclusion: Systemic manifestations were detected in 91.6% of children, while active arthritis was observed in 75% of patients, which can cause difficulties in the diagnosis and treatment of CAPS. The effectiveness of canakinumab therapy was estimated in 91.6% of patients. The most frequent variant of the NLRP3 gene in MWS was c.2113C>A . In patients with CINCA/NOMID syndrome all nucleotide variants were individual. Disclosure of Interests: Meyri Shingarova: None declared, Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Tatyana Dvoryakovskaya: None declared, Kirill Savostyanov: None declared, Aleksander Pushkov: None declared, Evgeniya Chistyakova: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Olga Lomakina: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Dariya Vankova: None declared, Elizaveta Krekhova: None declared, Ivan Kriulin: None declared, Natalia Zhurkova: None declared, Rustam Tepaev: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared